(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim : This study aims to evaluate the Flexural strength of novel drumstick gum powder reinforced epoxy composite and compare it with Sisal fiber reinforced epoxy composite. Materials and Methods: Sisal/Glass fiber with 10% and 20% volume fraction of novel drumstick gum powder reinforced epoxy composites were taken as an experimental group (N= 40). Sisal/Glass fiber epoxy composite was taken as a control group (N= 20). The hand layup technique was used to prepare the composites and flexural testing was conducted as per ASTM standard. G Power is taken as 80%. Results: The maximumflexural strength of Sisal/Glass fiber reinforced epoxy composite was observed as 74.2 MPa. The maximumflexural strength of Sisal/Glass fiber with 10% and 20% drumstick gum powder filler reinforced epoxy composite was observed as 75.1 MPa, 79.2 MPa. Among these three groups, composite with 20% filler showed statistically significant (p = 0.000; p<0.05) with filler adding composite. Conclusion: Within the limitations of this study, Sisal/Glass fiber with 20% volume fraction of novel drumstick gum powder filler reinforced epoxy composite exhibited improvement in flexural strength than Sisal/Glass fiber epoxy composite.